Wanita Karier Perspektif Islam (Upaya Membangun Keluarga Sakinah): Career Women in Islamic Perspective (Efforts to Build a Harmonious Family) - Ahmad Mutohar (Fenomena, 2014)
The modernity of science and technology development and growth will surely affect women's movements and activities, which from a legal perspective can introduce new variations in considering topics related to women's issues. Emancipation demands access to certain life sectors previously viewed as "taboo," leading to more lenient relationships. This has raised new concerns, necessitating continuous and proportional analysis. Modernitas perkembangan ilmu pengetahuan dan teknologi pasti akan memengaruhi gerak dan aktivitas wanita, yang dalam perspektif hukum dapat menjadi variasi baru dalam pertimbangan topik terkait masalah wanita. Emansipasi menuntut sektor-sektor kehidupan tertentu yang dulunya dianggap "tabu" untuk dimasuki oleh wanita, yang tampaknya memiliki hubungan yang lebih longgar. Hal ini menimbulkan kekhawatiran baru sehingga perlu dianalisis secara terus-menerus dan proporsional.